The Use of Google Translate in EFL Essay Writing: Is It a Cheating? - Puspa, Adelia; Saputra, Dwi Bayu; Haryana, Lia (Institut Agama Islam Negeri (IAIN) Curup, 2023)
During the process of writing an essay, many students are utilizing online translation tools like Google Translate due to the widespread availability of computing technology and the internet. Online translation programming is strong, yet it is inclined to over-exacting interpretation, and cannot represent the setting similar to a human interpreter. As a result, students are left to rely on a tool that promises to